ANALOG PROGRAMMABLE ELECTRONIC CIRCUIT- BASED CHAOTIC LORENZ SYSTEM - Rahma, Fadhil; Ali, Ramzy S.; Fortuna, Luigi (Basrah Journal for Engineering Sciences, 2014)
In this paper, we present a new chaotic circuit based on the dynamical system introduced by E. Lorenz in the Journal of the atmospheric sciences, Vol. 20, 130-141(1963). The design and implementation of the circuit are accomplished by using a field programmable analog array (FPAA). The implementation of chaotic Lorenz attractor discussed in this paper is not present in the literature. The experimental results shown in this paper demonstrate that the circuit exhibits pre-chaotic transient and chaotic Lorenz attractor.